Circular dichroism spectroscopy of DNA duplexes at near-biological concentrations. (1st July 2021) - Vanloon, Jesse; Harroun, Thad; Yan, Hongbin
Graphical abstract: Abstract: Circular dichroism (CD) of nucleic acids has been typically carried out at sample concentrations below 10 μ M, which is far lower than nucleic acid concentrations in biological systems. Attempts to study nucleic acid conformations by CD at higher concentrations using 10 and 1 mm pathlength cuvettes led to instrument artifacts. By shortening the light pathlength to around 0.1 mm, we herein report the first CD profiles of nucleic acids at sub-m M concentrations, which are relevant to nucleic acid concentrations in cellular cytoplasm and nucleus. These CD experimental conditions will allow future conformational studies of nucleic acids under biologically relevant conditions.